ESL Learners Reactions Towards Code Switching in Classroom Settings - Noli Maishara, Nordin; Farrah Dieba, Rashid Ali; Sharifah Intan Safina, Syed Zubir; Roslan, Sadjirin (Elsevier, 2013)
The use of more than one code of language among the Malaysian English language instructors and ESL learners in the context of formal classroom settings is widely acknowledged (Then & Ting, 2009). Many factors contribute to the occurrence of code-switching or in other words, there must have been certain communication purposes associated which cause code switching to occur. This study aims to uncover the attitudes of ESL learners towards the functions of code-switching employed by English language instructors at tertiary level. It addresses two research questions: (1) What do ESL learners think about code switching in the English classroom? (2) When does code switching best function in the English classroom for the ESL learners? Forty-five diploma students were randomly selected as the respondents for this study. A survey questionnaire which focused on the students” attitudes, usage and opinion towards code switching in the classroom was utilised in the study. It was found that most of the ESL learners have positive attitudes towards code switching. The ESL learners were also reported to believe that code switching facilitates them in understanding the target language. The findings suggest that the use of code switching is necessary when the situation requires the use of first language in the classroom to enable the learners to become more confident in mastering English.